1987
DOI: 10.3133/ofr85153
|View full text |Cite
|
Sign up to set email alerts
|

Hydrology of area 59, northern Great Plains and Rocky Mountain coal provinces, Colorado and Wyoming

Abstract: Hydrologic information and analysis aid in decisions to lease federally owned coal and to prepare necessary Environmental Assessments and Impact Study reports. This need has become even more critical with the enactment of Public Law 95-87, the "Surface Mining Control and Reclamation Act of 1977." This act requires an appropriate regulatory agency to issue permits, based on the review of permit-application data to assess hydrologic impacts. This report, which partially fulfills this requirement, is one in a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…The South Platte River Basin is characterized by a continental-type climate with wide temperature ranges and irregular seasonal and annual precipitation. Average monthly temperatures range from -30 to 100 degrees Fahrenheit (°F); temperatures increase from west to east and from north to south on the plains (Gaggiani et al, 1987). Temperatures are coldest during January and February and warmest during July and August.…”
Section: Climatementioning
confidence: 99%
“…The South Platte River Basin is characterized by a continental-type climate with wide temperature ranges and irregular seasonal and annual precipitation. Average monthly temperatures range from -30 to 100 degrees Fahrenheit (°F); temperatures increase from west to east and from north to south on the plains (Gaggiani et al, 1987). Temperatures are coldest during January and February and warmest during July and August.…”
Section: Climatementioning
confidence: 99%
“…The basin has a continental-type climate modified by topography, in which there are large temperature ranges and irregular seasonal and annual precipitation. Mean temperatures increase from west to east and on the plains from north to south (Gaggiani and others, 1987). Areas along the Continental Divide average 30 in.…”
Section: Physical Settingmentioning
confidence: 99%
“…The number of samples for each land use in the basin is shown in figure 36; only the agricultural site was fairly well sampled. Gaggiani and others (1987) concluded that not enough suspended-sediment data have been collected to compare to land-use practices. This is still true and needs to be addressed in future sampling programs.…”
Section: Description Of Datamentioning
confidence: 99%
“…During the study period, several seeps were discharging into Senac and Coal Creeks. MAXIMUM ANNUAL (1961-87) 1974197519771979198019811982PRECIPITATION, 1974-87 19831984198519861987 Figure 3.--Annual precipitation at Buckley Air National Guard Base, 1974-87.…”
Section: Geohydrologymentioning
confidence: 99%
“…Robson (1976) reported, and it was observed during drilling of bedrock wells in 1983 and 1984, that virtually all of the water in the bedrock wells came from the sandstone lenses. 13.94 ANNUAL PRECIPTATION IN INCHES 198119821984198519861987 Figure 4.--Quarterly precipitation at Buckley Air National Guard Base, 1981-87. the Senac Creek valley, the Coal Creek valley, and various smaller tributary valleys and hillside gullies, all of which are generally hydraulically connected. The Senac Creek alluvial aquifer follows the Senac Creek Valley diagonally through the middle of the sewage-sludge-disposal area, from the southeastern corner of section 9 to the northwestern corner of section 4.…”
Section: Geohydrologymentioning
confidence: 99%